Evaluation of environmental perception of the rural community of Tauari, Capanema - PA (Research, Society and Development, 2022)
Environmental perception can be defined as the way in which the individual perceives the environmental problems existing in his surroundings, enabling a better understanding of the concepts of the environment and acting in the development of skills of socio-environmental responsibility. In this way, this study aims to analyze the environmental perception of the residents of the rural community of the district of Tauari, located in the interior of the municipality of Capanema, state of Pará. This research was developed through the application of semi-structured questionnaires to the residents of the community, in addition to observations made by the researchers, as this helps to identify factors that the population itself is unaware of. It was identified that the community in the district of Tauari has a low socioeconomic development and a reasonable perception of environmental issues, often with distorted concepts about the practice of environmental education. Therefore, there was a need for the effective application of environmental practices in the community in order to encourage greater environmental awareness.